The Effect of Vitamin D Supplementation During Pregnancy on The Risk of Having Preterm Birth: An Evidence-based Case Report - Intan Meilana; Diyah Eka Andayani (Indonesian Nutrition Association, 2021)
Introduction: Preterm birth (PTB) is a major cause of neonatal morbidity and mortality. Pregnant women is one of the most vulnerable groups for vitamin D deficiency, that increase the risk of PTB. Vitamin D has the role of immunomodulator, anti-inflammatory, and transcription of genes involved in placental function. Research results on the correlation between vitamin D supplementation and PTB risk are still inconsistent.Objective: To observe the effect of oral vitamin D supplementation during pregnancy on the risk of PTBMethods: Advanced search for relevant literatures in PubMed, Cochrane, and Willey was conducted. After assessing the relevancy and eligibility, articles were selected and critically appraised.Results: There were three articles that relevant with the eligibility criteria and clinical questions, they were randomized controlled trial, meta-analysis and systematic review. Three studies found that oral vitamin D supplementation in the form of cholecalciferol during pregnancy had a significant reduction on the risk of PTB. A systematic review found that supplementation with combination of cholecalciferol and calcium carbonate may increase the risk of PTB. The different dosages, frequencies, and time of initiation limit the generalizations for efficacy and safety doses.Conclusion: Oral cholecalciferol supplementation during pregnancy reduces the risk of PTB. While supplementation with combination of cholecalciferol and calcium carbonate requires consideration. Further research is needed to find out about the dose, frequency, time of initiation, adverse events and effects of vitamin D when combined with other vitamins and minerals.Â Keywords: Pregnancy, vitamin D, vitamin D3, cholecalciferol, preterm birth, preterm labor.